Nanocomposites based on chitosan/silver/clay for durable multi-functional properties of cotton fabrics. (15th February 2018) - Rehan, Mohamed; El-Naggar, Mehrez E.; Mashaly, H.M.; Wilken, Ralph
Highlights: Development of green synthesis of chitosan based nanocomposites (Cs/AgNPs/clay). Cs/AgNPs/clay nanocomposite prove unequivocally one–step treatment for cotton fabrics. Cotton fabrics treated with Cs/AgNPs/clay exhibit high strength and uniform morphology. Treated cotton fabrics exhibit also enhancement in thermal stability. Furthermore, treated fabric exhibit antimicrobial activity, flame retardant and UV protection. Abstract: The present work addresses an innovative approach for benign development of environmentally synthesis of chitosan-based nanocomposite. The synthesis involves the inclusion via interaction of AgNPs and clay with chitosan (Cs) giving rise to Cs/AgNPs and Cs/AgNPs/clay nanocomposites which when applied independently induce super functionalities. Comparison is made among the two nanocomposites with respect to their intimate association with the in depth cotton fibre-fabric surfaces and the onset of this on the multi-functionalization of cotton fabrics. It is as well to emphasize that Cs/AgNPs/clay nanocomposites prove unequivocally that its use in one–step treatment process for cotton fabrics results in imparting very appreciable good technical properties which, in turn, are reflected on all the gained functionalities of cotton fabrics. Of these functional performance properties, mention is made of cotton fabrics which exhibit high strength, uniform morphology, increased thermal stability, successful deposition of the composite on the surface of cotton fabrics, high water absorption, antimicrobial activity, flame retardant, controlled release of fragrance and UV protection. The obtained data indicate that the treatment for cotton fabrics with these nanocomposite is stable against washing even after 20 washing cycles. Based on encourage data, the environmental benign synthesis of Cs/AgNPs/clay nanocomposites is considered as a promising nanocomposite for the multifunctional finishing textiles.